Now you see me, now you don’t: verifying the absence of alien invasive yellow crazy ant Anoplolepis gracilipes in South Africa - Ndaba, Abusisiwe; Munyai, Thinandavha Caswell; Mbanyana, Nokuthula; van Noort, Simon; Janion-Scheepers, Charlene (Frontiers in Insect Science, 2023)
Anoplolepis gracilipes is an invasive species that is a major threat to native ecosystems worldwide. It has been listed as one of the top 100 worst invasive species in the world and is well known for its negative impact on native arthropods and some vertebrates. This study aimed to confirm the presence or absence of A. gracilipes in some major South Africa habours. We did so by surveying four harbours in the Western Cape and KwaZulu-Natal, using pitfall trapping, yellow pan traps, and baiting. In addition, ant collections from Iziko Museums of South Africa (Cape Town, South Africa), University of KwaZulu-Natal (Pietermaritzburg campus, South Africa), Iimbovane Outreach Project (Stellenbosch University, South Africa), and AfriBugs CC (Pretoria, South Africa) were examined for specimens of A. gracilipes. The invasive species A. gracilipes was not detected from any of the sampled harbours during this study, nor in the main ant collections in South Africa. The only, and probably erroneous published record of A. gracilipes in South Africa is from Durban harbour and subsequent erroneously reported citizen science observations are from other coastal sites such as Gansbaai, Knysna, Table Bay, and Kalk Bay. This is a positive outcome for conservation authorities as this species is highly invasive and, if introduced, will likely outcompete native fauna and result in ecosystem collapse. Although A. gracilipes was not detected in the samples from this study, early detection and eradication of this species should be prioritised. This can be achieved through existing pest monitoring programs at harbours, and continued border biosecurity measures.